1986
DOI: 10.1111/j.1398-9995.1986.tb00341.x
|View full text |Cite
|
Sign up to set email alerts
|

Allergy Induced by Parietaria officinalis Pollen in Southern Croatia

Abstract: Pollen of Parietaria officinalis causes season-associated respiratory symptoms. In Southern Croatia (Yugoslavia) we found 65% patients with rhinitis and/or asthma to be allergic to this pollen. They showed positive cutaneous reactions and had specific IgE antibodies to the respective isolated allergen. The finding represents the first report on Parietaria officinalis-induced allergy on the east Adriatic coast.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

1989
1989
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 5 publications
0
11
0
1
Order By: Relevance
“…A similar situation arises with a member of the Urticaceae family. Because of its long pollen season and high levels of pollen, sensitive patients experience long-lasting symptoms that can be quite severe and difficult to treat (Cvitanovic et al 1986;Cvitanovic and MaruÐic 1994;Makra et al 2004Makra et al , 2006Makra et al , 2007. Pollen of the herbaceous plants of the Urticaceae predominated in July, whereas pollen of the most allergenic plant in the area, Artemisia sp., prevailed in August and September.…”
Section: Resultsmentioning
confidence: 98%
“…A similar situation arises with a member of the Urticaceae family. Because of its long pollen season and high levels of pollen, sensitive patients experience long-lasting symptoms that can be quite severe and difficult to treat (Cvitanovic et al 1986;Cvitanovic and MaruÐic 1994;Makra et al 2004Makra et al , 2006Makra et al , 2007. Pollen of the herbaceous plants of the Urticaceae predominated in July, whereas pollen of the most allergenic plant in the area, Artemisia sp., prevailed in August and September.…”
Section: Resultsmentioning
confidence: 98%
“…A similar situation arises with a member of the Urticaceae family, Parietaria officinalis. Because of its long pollen season and high levels of pollen, sensitive patients experience long-lasting symptoms that can be quite severe and difficult to treat (Cvitanović et al 1986;Cvitanović 1999;Cvitanović and MaruÐić 1994). Crossreactions to various allergenic pollen types from the family Poaceae lead to the manifestation of allergy in as many as 80% of allergic individuals.…”
Section: Discussionmentioning
confidence: 97%
“…Pollens appear seasonally and are reflected in the symptoms of patients with SR living in temperate climates. Recent studies have shown that grass pollen in Turkey [4,5,6,7,8], birch and grass pollens in northern Europe [17,18,19,20,21], ragweed pollen in America [22], and mugwort and olive pollens in the Mediterranean area [23,24,25,26,27] are the most common and important allergens of these regions. Since Turkey is located between Europe and Asia like a bridge, all four seasons can be present in different regions of the country at the same time of the year.…”
Section: Discussionmentioning
confidence: 99%